1966
DOI: 10.1002/aic.690120516
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal dispersion mechanisms in packed beds

Abstract: A theoretical study has been mode of longitudinal dispersion mechanisms during steady flow of o fluid through unconsolidated spherical beads. The mathematical model utilizes a step function input of thermal energy and presents the solution for the transient behavior of the system. The longitudinal dispersion of the step input is considered the result of eddy mixing of the fluid, molecular conduction within the fluid, and a finite time log for heat transfer to occur between fluid and particle. The latter mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 15 publications
(4 reference statements)
1
14
0
Order By: Relevance
“…Rosen presented a solution for the case, what he called it a general problem of the transient behavior of a linear fixed-bed system where the rate of adsorption is determined by the combined effect of a liquid film and solid diffusion into spherical particles [6]. Babcock, Green and Perry made a theoretical study about the longitudinal dispersion mechanism during the steady flow of a fluid through unconsolidated spherical beads [7]. Rasmuson In the current study, hydrogen fluoride (HF) adsorption onto the sodium fluoride pellets is modeled.…”
Section: Introductionmentioning
confidence: 99%
“…Rosen presented a solution for the case, what he called it a general problem of the transient behavior of a linear fixed-bed system where the rate of adsorption is determined by the combined effect of a liquid film and solid diffusion into spherical particles [6]. Babcock, Green and Perry made a theoretical study about the longitudinal dispersion mechanism during the steady flow of a fluid through unconsolidated spherical beads [7]. Rasmuson In the current study, hydrogen fluoride (HF) adsorption onto the sodium fluoride pellets is modeled.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been necessary to examine critically the conditions proposed earlier by Handley and Heggs (9) and by Babcock and co-workers (2,3 ) .…”
Section: Applicability Of Single Parameter Modelsmentioning
confidence: 99%
“…An alternative parameter known as the bed length parameter, yx has been used by Rosen and Babcock et al (2,3) as a measure of the relative importance of internal particle conduction. This parameter, also known as the "effective bed length," is simply the ratio of the transfer parameter Y to the particle Biot number Handley and Heggs (9) have suggested that internal particle conduction effects may be ignored when the value of the bed length parameter is greater than 60.…”
Section: Effects Of Internal Particle Conductivitymentioning
confidence: 99%
“…Moench [12], in his study of doubly-porous groundwater reservoirs, incorporated the effects of a thin layer of low permeable material or fracture skin which may be present at fracture-block interfaces. Babcock et al [2] developed a model for longitudinal dispersion mechanisms during steady flow of a fluid through unconsolidated spherical beads which include a stagnant fluid film surrounding the particle. Skopp and Warrick [14] studied miscible displacement by considering there to be a mobile phase and a stationary phase, whereby solute transfer occurs through the mobile phase via convection, and through the stationary phase via diffusion.…”
Section: Literature Reviewmentioning
confidence: 99%